Genetics of the pig [ - Rothschild, Max Frederick , 1952-; Ruvinsky, Anatoly (CABI, 2011)
The understanding of pig genetics and genomics has advanced significantly in recent years, creating fresh insights into biological processes. This comprehensive reference work discusses pig genetics and its integration with livestock management and prodction technology to improve performance. Fully updated throughout to reflect advances in the subject, this new edition also includes new information on genetic aspects of domestication, colour variation, genomics and pig breeds, with contributions from international experts active in the field.